2017
DOI: 10.1111/1556-4029.13631
|View full text |Cite
|
Sign up to set email alerts
|

Controversial Suicide Case Using a Submachine Gun with a Sound Suppressor—The Need of Team Work of Forensic Chemistry and Firearm Examiners

Abstract: Evidence materials in a presumed suicide case were studied by a firearm examiner and a forensic chemist. The victim's body with double gunshot wounding in his forehead, a machine gun in the sustained fire mode with a silencer, and four cartridge cases were found. Examinations of the evidence, the case file studies, and experiments dedicated to the case were carried out. Relationships between the placement of cartridge cases and the gun were established using a fast camera. The distributions of gunshot residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…These detailed examinations of the array of shooting patterns depending on the shooting distance in the range of 0–30 cm, being included in the category of close-range distance, 27 were performed to be able to compare the GSR distribution with other similarly performed examinations, however, for different kinds of ammunition. The common property of GSR distribution obtained in the current study with these published earlier both for small arms 10,15,20,28 and also for a cal. 12 23 rifle was the relatively great amount of lead particles that most probably originated mainly from the lead core of the projectile and a smaller amount from the primer components.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These detailed examinations of the array of shooting patterns depending on the shooting distance in the range of 0–30 cm, being included in the category of close-range distance, 27 were performed to be able to compare the GSR distribution with other similarly performed examinations, however, for different kinds of ammunition. The common property of GSR distribution obtained in the current study with these published earlier both for small arms 10,15,20,28 and also for a cal. 12 23 rifle was the relatively great amount of lead particles that most probably originated mainly from the lead core of the projectile and a smaller amount from the primer components.…”
Section: Resultssupporting
confidence: 89%
“…26 However, the application of a 5 cm radius provides meaningful results for the analysis of various properties of GSR depending on the shooting distance. 10,15,20…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, studies modeled on real-life cases emphasize the relevance of GSR for forensic investigators. Brożek-Mucha and Zdeb conducted a study regarding a purported suicide case in which the weapon was a machine gun . The GSR in this case was studied using a variety of techniques.…”
Section: Gunshot Residuementioning
confidence: 99%
“…Brozėk-Mucha and Zdeb conducted a study regarding a purported suicide case in which the weapon was a machine gun. 166 The GSR in this case was studied using a variety of techniques. Overall, researchers found that, on the basis of the evidence, including the GSR distribution, the case appeared to be more likely a homicide than a suicide.…”
Section: Analytical Chemistrymentioning
confidence: 99%